INCIDENCE AND MANAGEMENT OF ADVERSE RESPIRATORY EVENTS IN THE POST-ANESTHESIA CARE UNIT: A CROSS-SECTIONAL STUDY (Journal of Medical & Health Sciences Review, 2025)
Background: Adverse respiratory events (AREs) are among the most common complications encountered in the Post-Anesthesia Care Unit (PACU), often resulting in increased morbidity, prolonged recovery, and higher healthcare resource utilization. Early recognition and effective management are essential to improving postoperative outcomes.Objective: To determine the incidence, risk factors, and management strategies associated with adverse respiratory events in the PACU.Methodology: A prospective observational study was conducted in the PACU of a tertiary care hospital over six months. Adult patients undergoing general anesthesia were monitored for the occurrence of AREs, including hypoxemia, airway obstruction, apnea, and bronchospasm. Data on patient demographics, comorbidities, type of surgery, anesthetic techniques, and interventions used were collected and analyzed.Results: Among 186 patients assessed, 112 (28%) experienced one or more AREs. Hypoxemia was the most frequent event (13.5%), followed by airway obstruction (8.5%) and respiratory depression (4.5%). Significant associations were found with factors such as ASA classification, BMI >30, smoking history, and pre-existing respiratory conditions (p